Identifikasi Sebaran dan Karakter Tanaman Leci sebagai Tanaman Lansekap di Tepi Jalan Raya Payangan, Kecamatan Payangan, Kabupaten Gianyar - SAPTAYANA, I WAYAN; SUDARSANA, A.A. GEDE DALEM; SUKEWIJAYA, I MADE (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017DO - 10.24843/JAL.2017.v03.i01.p08, 2017)
ABSTRACT The Identification of Distribution and The Character of Lychee as The Landscape Plant in Sides of The Jalan Raya Payangan, The District of Payangan, Gianyar Regency Lychee plants in Bali are plants that introduced from China, that is comes from Guangdong and Fujian. Although this plant is not as an original plant from Indonesia and classified as rare plant, however it has been established as flora of the identity of Gianyar Regency. Lychee plant is one of the many types of trees that grown along to Jalan Raya Payangan. However, nowadays, its existence has been reduced. This study aims to find out the distribution and appropriateness of the character of lychee as landscape plants in Payangan, Gianyar Regency. This research was using survey method with data collection technique, by field observation, interview, questionnaires and literature study. The final result of research shows that 14,5 km in Jalan Raya Payangan, there are 18 species of plants as framer of landscape in Payangan. There are 42 lychee plants that still growing properly and there are five filling formers of lychee trees. Based on the combination of the technical reference Direktorat Jendral Bina Marga (1996), Steenis (2005), and Carpenter, (2000), there are nine terms of plants that required being landscape plant on sides of the roads, but from nine terms the research founded that lychee plants only requiring five terms, about that lychee plants unfit as landscape plant on sides of the Jalan Raya Payangan, The District of Payangan, Gianyar Regency. Keywords: lychee plant, character, landscape plants, Payangan, Gianyar.